The role of populist strategies in differing outcomes of corruption scandals in Brazil and Turkey - Onbasi, Nilay (Routledge Journals, Taylor & Francis Ltd, 2020)
The Workers' Party (Partido dos Trabalhadores - PT) in Brazil and the Justice and Development Party (Kalkinma ve Adalet Partisi - AKP) in Turkey came to power in 2002 with promises of maintaining economic growth, social justice and political stability. Initially, both governments experienced some success. However, both countries experienced political turmoil as a result of the corruption allegations in the early 2010s. This study compares these cases to analyze what allowed the AKP government to cover up and overcome the corruption allegations whereas the PT government could not. This study concludes that populist characteristics in political strategies of Turkey's President Erdogan allowed him to maintain his ruling through suppression of all opposition movements and voices, while Brazilian President Rousseff did not implement the same strategies and consequently lost power.
Keywords: Corruption; populism; AKP; PT; Turkey; Brazil